The Effects of Firm-Specific Factors on the Financial Soundness by using CARAMELS Framework Indicators: A Case of Non-Life Insurance Industry of Pakistan - Nadir Ali; Zahid Ali Chanar; Saghir Pervaiz Ghauri; Shahid Obaid (Institute of Business Management, 2019)
The study is carried out to identify the relations of firm-specific factors with the financial soundness indicators of CARAMELS framework for the non-life insurance industry, by using a panel data set of 22 non-life insurance companies of Pakistan from 2007 to the year 2016. This study is established on two most applicable panel data techniques (random effects as well as fixed effects models), referring to the Hausman's test. This test proves that the fixed effect model is appropriate for the analyses of firm-specific factors. Based on the highest number of relationships among variables, fixed effects model's results propose that three firm-specific factors (age of company, management competence index and operating ratios) have significant relations with the CARAMELS financial soundness indicators. However, seven firm-specific factors (size of the company, equity capital, leverage, market share, investment ratio, premium growth and solvency margin) have insignificant relation with the CARAMELS financial soundness indicators. According to author's best knowledge, it's the first study that identifies the relations of firm-specific factors with the CARAMELS financial soundness indicators, that will assist to the scholars, managers and policymakers of the non-life insurance industry of Pakistan to consider the significant factors.